Avaliação de pacientes classe III submetidos à expansão e protração maxilar através de dois diferentes protocolos de expansão: controle de 12 meses - Gourgues, Lisandra Jacomelli (2012)
Introduction: The purpose of this study was to evaluate and compare changes skeletal, dental, and soft tissue profile on the anteroposterior two protocols due to maxillary expansion and protraction of the maxilla in 12 months. Methods: a sample of 19 patients (mean age 7 to 14 years) underwent maxillary expansion and protraction hyrax appliance) and randomly divided into 2 groups: (1) Group ERMC (n=10) and (2) Group ERM (n=9). All patients had an initial activation of the expansion of 0.8 mm (4/4 turn). From the second day of activation did patients in Group 1 (ERMC) performed daily activations of 2/4 back in the morning and 2/4 back at night, making a total of 4/4 back daily, and was held the following week off to screw the same amount daily. This protocol was repeated for 7 weeks followed by 6 months of maxillary protraction. For Group 2 (ERM), the screw was activated from the second day of activations: 2/4 back in the morning and 2/4 back in the evening, making a gap of 5.6 mm at the end of seven days, then 6 months of maxillary protraction. Cephalometric measurements were made at different times: pretreatment (T1); immediately after expansion (T2); 6 months of treatment (T3) and after 6 months of contention with the use of the mask (T4). These measurements were evaluated using mixed model with symmetric covariance followed by Tukey-Kramer test (5% level). Results: after 12 months of treatment there was displacement of the jaw down and forward, mandibular rotation down and back, with an increase in lower face, promoting better maxillomandibular relation and soft tissue profile of individuals. Conclusion: There was no difference between the two protocols studied expansion, followed by protraction, when evaluated the effects anteroposterior in 12 months of treatment.